Physiology of thermoregulation during swimming - Neilsen, B. (1977)
Body temperature is balanced between heat produced and lost by conduction, convention, radiation, and evaporation. When heat lost is less than that produced, temperatures will fall. When heat incurred is more than that dissipated, temperatures will rise. In water, heat is carried away much more effectively than in air due to both conduction and convection. In low air temperatures, shivering can increase heat production by two to three times and strenuous exercise could add another ten-fold increase over normal. With continued severe exposure to the cold, central core temperature falls due to continued heat loss because heat is lost to the environment faster than it can be generated internally. The body's ability to combat heat loss is impaired at body temperatures below 35 degrees Celsius, with symptoms such as euphoria and loss of reasoning being common. All control is lost below 28 degrees Celsius. Despite other survival responses aimed at raising body temperature, body temperature will continue to fall in cold water, the rate of decline being dependent upon water temperature, activity level, and insulating fat layers. Core temperature can start to fall in water temperatures between 18 and 21 degrees Celsius. In water as warm as 32 degrees Celsius, body heat cannot be dissipated fast enough and rises. When it is slightly warmer (e.g., 34 degrees Celsius) dangerous internal temperatures will be reached in approximately 30 minutes of moderate sustained exercise.